Legal Barriers Affecting Decentralized Public Service Delivery in Rapidly Transforming Political Environments - Dian Karisma (Universitas Sains dan Teknologi Komputer, 2025)
Public service delivery through decentralization is meant to improve administrative effectiveness, but its implementation still faces legal ambiguity amid a constantly evolving political landscape. This research study proposes to examine the impact of legal impediments on the efficiency of implementing the legal framework for public service delivery through decentralization. The research will make use of the normative-empirical legal methodological framework. This uses the doctrinal research method, drawing on data collected from 30 local officials who provide the service under the legal framework of decentralization. The findings indicate that legal barriers take three forms: normative barriers arising from unclear implementing rules, structural barriers stemming from overlapping central and local authority, and implementation barriers arising from risk-averse bureaucracy. These challenges are exacerbated by political dynamics, which increase the likelihood of legal uncertainty and, in turn, of ineffective service delivery. The project will therefore make a theoretical contribution to the literature on the role of legal barriers to decentralization, the political dynamics that mediate them, and the outcomes of decentralized governance. More specifically, it will underscore the importance of harmonizing regulations and strengthening legal frameworks to enhance legal certainty in decentralized public administration. Finally, it is concluded that legal barriers are crucial to ensuring the effectiveness and accountability of decentralization in public service delivery.